Integrated Microbiome and Metabolome Analysis Reveals a Positive Change in the Intestinal Environment of Myostatin Edited Large White Pigs - Pei, Yangli; Chen, Chujie; Mu, Yulian; Yang, Yalan; Feng, Zheng; Li, Bugao; Li, Hua; Li, Kui (Frontiers in Microbiology, 2021)
Myostatin (MSTN) functional inactivation can change the proportion of lean meat and fat content in pigs. While both genotype and microbial composition are known to affect the host phenotype, so far there has been no systematic study to detect the changes in the intestinal microbial composition and metabolome of MSTN single copy mutant pigs. Here, we used 16S rDNA sequencing and metabolome analysis to investigate how MSTN gene editing affects changes in the microbial and metabolome composition in the jejunum and the cecum of Large White pigs. Our results showed that Clostridium_sensu_stricto_1, Bifidobacterium, Lachnospiraceae_UCG-007, Clostridium_sensu_stricto_6, Ruminococcaceae_UCG-002, and Ruminococcaceae_UCG-004 were significantly upregulated; while Treponema_2 and T34_unclassified were significantly downregulated in the jejunum of MSTN pigs. Similarly, Phascolarctobacterium, Ruminiclostridium_9, Succinivibrio, Longibaculum, and Candidatus_Stoquefichus were significantly upregulated, while Barnesiella was significantly downregulated in the cecum of MSTN pigs. Moreover, metabolomics analysis showed significant changes in metabolites involved in purine, sphingolipid and tryptophan metabolism in the jejunum, while those associated with glycerophospholipid and pyrimidine metabolism were changed in the cecum. Spearman correlation analysis further demonstrated that there was a significant correlation between microflora composition and metabolites. Our analyses indicated the MSTN editing affects the composition of metabolites and microbial strains in the jejunum and the cecum, which might provide more useable nutrients for the host of MSTN± Large White pigs.